Free-Breathing and Ungated Cardiac MRI Reconstruction Using a Deep Kernel Representation - Qing Zou; Abdul Haseeb Ahmed; Sanja Dzelebdzic; Tarique Hussain (Applied Sciences, 2023)
Free-breathing and ungated cardiac MRI is a challenging problem due to the cardiac motion and respiration motion, which are not tracked. In this work, we propose an unsupervised deep kernel method for reconstructing real-time free-breathing and ungated cardiac MRI from highly undersampled k-t space measurements. We propose implementing the feature map and kernel function in the kernel method using CNNs. The parameters of the CNNs are learned from specific-subject data directly. Comparisons with state-of-the-art kernel methods show improved performance of the proposed deep kernel method.